Clinical impact of nasal budesonide treatment on COPD patients with coexistent rhinitis - Calabrese C (International Journal of COPD, 2018)
Cecilia Calabrese,1 Adriano Costigliola,1 Marianna Maffei,2 Vittorio Simeon,3 Francesco Perna,4 Eugenio Tremante,2 Elena Merola,5 Carlo Antonio Leone,2 Andrea Bianco1 1Department of Cardio-Thoracic and Respiratory Sciences, Monaldi Hospital, University of Campania “Luigi Vanvitelli”, Naples, Italy; 2Ear Nose and Throat Unit and Neck Surgery, Monaldi Hospital, Naples, Italy; 3Medical Statistics Unit, University of Campania “Luigi Vanvitelli”, Naples, Italy; 4Department of Clinical Medicine and Surgery, Monaldi Hospital, University “Federico II”, Naples, Italy; 5Bronchoscopic Unit, Public Hospital, Eboli, Italy Background: A high percentage of patients with COPD report chronic nasal symptoms. The study aims to evaluate the clinical impact of a 2-month treatment with inhaled nasal budesonide (100 µg per nostril twice daily) in patients affected by COPD with chronic rhinitis comorbidity.Patients and methods: Fifty-three stable COPD patients in therapy according to the Global initiative for chronic Obstructive Lung Disease recommendations were enrolled; 49 completed the study. At enrollment (visit 0), patients underwent skin prick test and rhinoscopy. At visit 0 and after 1 month (visit 1) and 2 months (visit 2) of therapy with nasal budesonide, patients underwent spirometry, and COPD assessment test (CAT), Sinonasal Outcome Test (SNOT 22), and modified Medical Research Council dyspnea scale were administered. Differences in continuous variables, after 2 months of treatment with nasal budesonide, were evaluated using a paired t-test or Wilcoxon matched-pairs signed-ranks test.Results: Two months of treatment with nasal budesonide showed a significant statistical improvement in the total scores of CAT, SNOT 22, and modified Medical Research Council (p<0.001). A significant relationship between CAT and SNOT 22 total scores at baseline and after treatment was observed.Conclusion: The results of the present study indicate the importance of careful evaluation of the presence of chronic nasal symptoms in all COPD patients and suggest beneficial clinical effect from treatment with nasal budesonide in terms of COPD symptoms and quality of life. Keywords: COPD, rhinitis, CAT, SNOT 22, mMRC, budesonide